Fish community structure as a function of habitat structure on West Indian patch reefs - Gladfelter, William B. (Universidad de Costa Rica, 1978)
The fish communities of twenty-five natural patch reefs in a back-reef lagoon off northeastern St. Croix, West Indies, were censused visually during summer, 1976. These reefs fell into two morphologically distinct groups: those in the east were of consolidated carbonate pavement reaching to near the water surface; those in the west consisted of scattered large coral heads (Porites porites and Montastrea annularis) separated by sand, and in slightly deeper water. Indices of similarity were calculated for the fish faunas of all pairs of reefs based on comparisons of abundances of all species present. The resulting matrix was used to construct a dendrogram of fish faunal similarity, which corresponded to major differences in the physical makeup of the reefs. Among structurally similar reefs, fish faunas were very similar, with forty-five species distributed uniformly among similar reefs. The majority of the remaining species were rare and local or uncommon. The distribution of some of the species could be correlated with single distinctive physical parameters of the reefs such as the presence of vertical walls, caves or the proximity to oceanic water or with biological factors such as food availability. When categorized according to general trophic category, omnivores were most abundant, followed by herbivores, crustacean eaters, planktivores (nearly all nocturnally active species), piscivores, and species with other, specialized diets (e. g. sponges). Although the morphologically most dissimilar reefs collectively had the most dissimilar fish faunas, the overall trophic composition of the eastern and western groups of reefs was similar.